2003
DOI: 10.1046/j.1464-410x.2003.04079.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy transurethral microwave thermotherapy: symptomatic vs urodynamic success

Abstract: RESULTSAll patients completed at least 1 year of follow-up after TUMT as monotherapy. The symptom score improved from a median (range) of 20.5 (11-28) initially to 9 (0-28) ( P < 0.001). Twenty-two patients (55%) had a marked and 11 (28%) a moderate response, giving an overall subjective success rate of 83%. Similarly, there was a significant improvement in peak flow rate, from 9.2 (4.4-13.4) to 15 (3.3-22.9) mL/s ( P < 0.001). Twenty-one patients (53%) had a maximum flow rate of > 15 mL/s while in eight (20%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Heat penetration in the prostate depends on the water content of the different types of tissues, and the frequencies and exposure time used for application. [24][25] Moreover, low-energy treatments seem to be inadequate to obtain satisfactory results, in terms of the ability to induce necrosis and subsequent reduction of urinary outlet obstruction. [26][27] On the other hand, high-energy treatments gave good results in terms of improvement in urinary obstruction, but are burdened with increased morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Heat penetration in the prostate depends on the water content of the different types of tissues, and the frequencies and exposure time used for application. [24][25] Moreover, low-energy treatments seem to be inadequate to obtain satisfactory results, in terms of the ability to induce necrosis and subsequent reduction of urinary outlet obstruction. [26][27] On the other hand, high-energy treatments gave good results in terms of improvement in urinary obstruction, but are burdened with increased morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al [18] treated men with TUMT (Targis device, high energy) and reviewed predictors of urodynamic and symptomatic success. They used PFUDs-grading obstruction based on Schäfer's nomogram-and found that higher grade obstruction rather than free-fl ow rate predicted symptomatic improvement after treatment.…”
Section: Transurethral Microwave Heat Treatmentmentioning
confidence: 99%